Health Literacy with Quality of Life in People with HIV AIDS - Rahmawati, Rahmawati; Sunarsih, Sunarsih; Komang Ayi Sukma; Fitri Yanti; Sri Mulyani (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Indonesia is the 5th most vulnerable country in Asia, with an accumulated number of 519,158 cases in 2022. Health literacy is essential for people with HIV/AIDS (PLWHA) to avoid opportunistic infections through increased insights related to their health care. This study aims to analysing the relationship between respondent characteristics and access to information with health literacy and the relationship of health literacy with the quality of life of HIV/AIDS sufferers. Methods: Cross-sectional studies are used in this kind of quantitative research. The population in this study is 316 people with PLWHA undergoing treatment at Kendari City Hospital in 2023, with a sample of 177 people. Sampling of the study used Simple Random Sampling. The data analysis used is the Chi-Square Test. Results: The results of the study were obtained from the Chi Square test based on gender, p-value (0.769) > ? (0,05), based on age p-value (0.598 > ? (0,05), based on education p-value (0,004) < ? (0,05), based on the length of suffering p-value (0,006) < ? (0,05), and based on access to information p-value (0,001) < ? (0,05). The results of the binary logistic regression analysis were obtained by the information access variable with Exp (B) = 3,222. Conclusion: Factors related to health literacy in people with HIV/AIDS are education, long-time suffering and access to information. Health literacy related to quality of life in people with HIV/AIDS at Kendari City Hospital. It is expected, the hospitals which are the basis for health information services for PLHIV need to improve health literacy programs both conventionally and electronically involving digital technology.